Between-hospital and between-neighbourhood variance in trauma outcomes: cross-sectional observational evidence from the Detroit metropolitan area. Issue 11 (25th November 2018) - Sall, Lauren; Hayward, R David; Fessler, Mary M; Edhayan, Elango
Abstract : Objective: Disparities in treatment outcomes for traumatic injury are an important concern for care providers and policy makers. Factors that may influence these disparities include differences in risk exposure based on neighbourhood of residence and differences in quality of care between hospitals in different areas. This study examines geographical disparities within a single region: the Detroit metropolitan area. Design: Data on all trauma admissions between 2006 and 2014 were obtained from the Michigan State Inpatient Database. Admissions were grouped by patient neighbourhood of residence and admitting hospital. Generalised linear mixed modelling procedures were used to determine the extent of shared variance based on these two levels of categorisation on three outcomes. Patients with trauma due to common mechanisms (falls, firearms and motor vehicle traffic) were examined as additional subgroups. Setting: 66 hospitals admitting patients for traumatic injury in the Detroit metropolitan area during the period from 2006 to 2014. Participants: 404 675 adult patients admitted for treatment of traumatic injury. Outcome measures: In-hospital mortality, length of stay and hospital charges. Results: Intraclass correlation coefficients indicated that there was substantial shared variance in outcomes based on hospital, but not based on neighbourhood of residence. Among all injury types, hospital-level differences accounted for 12.5% of variance in mortality risk, 28.5% of variance in length of stay and 32.2% of variance in hospital charges. Adjusting the results for patient age, injury severity, mechanism and comorbidities did not result in significant reduction in the estimated variance at the hospital level. Conclusions: Based on these data, geographical disparities in trauma treatment outcomes were more strongly attributable to differences in access to quality hospital care than to risk factors in the neighbourhood environment. Transfer of high-risk cases to hospitals with greater institutional experience in the relevant area may help address mortality disparities in particular.